Remission of Severe, Relapsed, and Refractory TTP after Multiple Cycles of Bortezomib - Manu R. Pandey; Pankit Vachhani; Evelena P. Ontiveros (Case Reports in Hematology)
Acquired thrombotic thrombocytopenic purpura (TTP) is characterized by autoantibodies against a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13). Uncleaved von Willebrand factor (VWF) multimers accumulate and bind to platelets which causes spontaneous microthrombi ultimately causing microangiopathic hemolytic anemia, thrombocytopenia, and end-organ ischemia. Plasma exchange (PEX) with or without steroids constitutes standard first-line therapy with rituximab typically reserved for refractory cases. Therapies beyond rituximab lack strong evidence for routine use. Recently, bortezomib, a proteasome inhibitor used commonly in patients with multiple myeloma, was shown to induce remission in patients with refractory TTP. Here, we report a case of severe, relapsed TTP that was refractory to PEX, steroids, and rituximab that underwent remission following three cycles of bortezomib. We discuss the salient features of our case, the mechanism of action of bortezomib, and the very few other similar reports that exist in the literature. We conclude that bortezomib should be considered for patients with TTP refractory to PEX, steroids, and rituximab due to its efficacy and relatively favorable side effect profile.